Обозначим x массу первого раствора, тогда масса второго (600 - x).
Составим уравнение:
0,3x + 0,1* (600 - x) = 600 * 0,15;0,3х + 60 - 0,1х = 90 0,2х = 3
x = 150 ( г.) масса 1 раствора
600 - 150 = 450 (г.) масса 2 раствора
450-150 = 300 (г.)
Ответ: на 300 г. масса 1 раствора меньше массы 2 раствора
Составим уравнение:
0,3x + 0,1* (600 - x) = 600 * 0,15;0,3х + 60 - 0,1х = 90 0,2х = 3
x = 150 ( г.) масса 1 раствора
600 - 150 = 450 (г.) масса 2 раствора
450-150 = 300 (г.)
Ответ: на 300 г. масса 1 раствора меньше массы 2 раствора